The Effectiveness of Shared Reading Strategy toward Students’ Reading Achievements - Hutabarat, Berni Arnita; Pohan, Albert Effendi; Adam, Adam (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2017)
Many students got difficulty in reading descriptive text, especially who lack on vocabulary. To acquire the students’ reading comprehension, it is needed to stimulate the students’ mind and corrective feedback. Thus, to solve this problem, the writer tried to teach reading descriptive text by using Shared Reading Strategy to make the reading activity in the classroom more effective and could improve students’ reading comprehension. The writer conducted this teaching media in process of reading descriptive text at class VII-A at SMP Tunas Baru Jin – Seung Batam with 35 samples. This research is a quantitative approach. The method was used in this research is experiment method and focused on Quasi experimental. The research conducted in SMP Tunas Baru Jin – Seung Batam, on April – June 2016 where two classes were taken as the samples of this study. Class VII-A as experimental class and VII-B as control group. The technique of collecting data in this research was pre-test and post-test. The question in pre-test and post-test are similar form. To prove that the alternative hypothesis (Ha) is accepted, the researcher used t-test formula calculate the data. The data gained Ttestt table(31.641.667). It also can be seen from both classes post-test mean value; control class’ mean was 69 and experimental class’ was 78.43. So, it can be concluded that the used of Shared Reading Strategy gives a significant effect in student’s reading comprehension. Keywords: students reading comprehension, shared reading strategy.